Development of an autonomous vehicle highway merging strategy. (1st January 2012) - Kim, Changwon; Langari, Reza
In this paper, we propose a highway merging method to enhance vehicle autonomy in the highway travelling. The proposed decision making algorithm includes a Modified Intelligent Driver Model (MIDM) based vehicle distance adjustment and path prediction for collision avoidance. In order to maximise the safety and driving efficiency, a time optimal target is selected when the front and rear gap conditions that secure the merging safety are not satisfied. The suggested algorithm is implemented by a lane change manoeuvre and Adaptive Cruise Control (ACC) that are based on a control strategy inspired by the brain limbic system. In order to demonstrate the performance of the suggested merging strategy, the concept of Level of Service (LOS) is utilised in the simulations.